Camino island ebook - Grisham, John (Camino Island, 2017)
#1 NEW YORK TIMES BESTSELLER • Soak up the sun—and the intrigue—with the first novel in John Grisham’s beloved Camino series. “A happy lark [that] provides the pleasure of a leisurely jaunt periodically jolted into high gear, just for the fun and speed of it.”— The New York Times Book Review A gang of thieves stage a daring heist from a secure vault deep below Princeton University’s Firestone Library. Their loot is priceless, but Princeton has insured it for twenty-five million dollars.   Bruce Cable owns a popular bookstore in the sleepy resort town of Santa Rosa on Camino Island in Florida. He makes his real money, though, as a prominent dealer in rare books. Very few people know that he occasionally dabbles in the black market of stolen books and manuscripts. Mercer Mann is a young novelist with a severe case of writer’s block who has recently been laid off from her teaching position. She is approached by an elegant, mysterious woman working for an even more mysterious company. A generous offer of money convinces Mercer to go undercover and infiltrate Bruce Cable’s circle of literary friends, ideally getting close enough to him to learn his secrets. But eventually Mercer learns far too much, and there’s trouble in paradise as only John Grisham can deliver it. Look for all of John Grisham’s rollicking Camino novels: Camino Island Camino Winds Camino Ghosts